Solving the Two-Level Hierarchical Covering Location Problem with an Electromagnetism-Like Metaheuristic - Milivojević Danas, Milica; Bogdanović, Milena (Computing and Informatics, 2024)
In this paper, an electromagnetism-like approach (EM) for solving the two-level hierarchical covering location problem (TLHCLP) is proposed. An EM metaheuristic is a powerful algorithm for global optimization that converges rapidly to the optimum. Therefore, it has the potential to solve this type of problem since movement based on the attraction-repulsion mechanisms, combined with the proposed scaling technique, directs EM to promising search regions. The fast implementation of the objective function and local search procedure for TLHCLP additionally improves the efficiency of the overall EM system. The proposed EM approach reaches all optimal solutions in a relatively short amount of computational time. EM also obtains high-quality solutions for large-scale problem instances that are out of reach for exact methods.